Food Safety, the Environment, and Trade - Zilberman, David; Hochman, Gal; Sexton, Steven E. (World Bank, Washington, DC, 2017)
In this paper, the authors discuss the ways in which national governments, firms, and individuals respond to policy related to food safety, environmental protection, and trade. These responses must be considered in the development of policy to ensure the best possible outcomes. It accounts for uncertainty about policy impacts and scientific knowledge and incorporates stochastic environmental factors. The authors argue use of such a model in the development of health and environmental policy can overcome capture by domestic forces opposed to trade liberalization. The effectiveness of policy, of course, is dependent upon firm and consumer response to policy. Section one describes the impacts of international transfer of species and genetic material, paying particular attention to the introduction of alien invasive species. Section two discusses issues surrounding trade in environmental amenities. Food safety and environmental regulations are reviewed in section three, along with mechanisms by which such policy can serve as a proxy for protectionists. Section four develops a risk assessment model that can be used in policy design. Section five considers the role of institutional, firm and individual behavior in the development and effectiveness of policy. Section six summarizes our analysis in offering an agenda for trade talks.